Analysis of the application of functional near-infrared spectroscopy in acupuncture research: a review - Xu, Jili; Tang, Xing; Liu, Xiaotong; Wang, Yi; Wu, Jie (Frontiers in Neurology, 2025)
Acupuncture, as an effective external treatment method, has been widely used in various clinical diseases, but the research on its mechanism still needs to be further deepened. Functional near-infrared spectroscopy (fNIRS) technology, as an emerging non-invasive neuroimaging technique, has the advantages of high timeliness, wide application scenarios, good portability and low cost. Currently, it is widely used in the mechanism research of acupuncture. This paper reviewed all the studies on the application of fNIRS in acupuncture, analyzed and summarized the current application status of fNIRS technology in acupuncture research. Firstly, we elaborated on the working principle of fNIRS and highlighted its advantages in acupuncture research and application. Secondly, we detailed the specific applications of fNIRS in acupuncture research. Finally, we discussed the existing problems of fNIRS in acupuncture research at present and the improvement directions for future research.